Pengelolaan Genangan Air Dangkal untuk Meningkatkan Hasil Padi dengan Kerangka Kerja System of Rice Intensification (SRI) - Maftukhah, Rizki; Erni R, -; Purwanto, Benito Heru; Sri R, -; Arif, Sigit Supadmo (Balai Teknik Irigasi, 2015)
Nowadays, the issues of water scarcity, high fertilizer cost, and negative environmental impacts due to high agrochemicals use are escalating so that the improvement of resource efficiency on rice cultivation is necessary. Based on many studies, SRI is a very promising approach. Pot experiment was conducted under SRI framework with continuous flooding (CF), shallow water depth (SWD), and field capacity (FC) irrigation; together with four different doses of organic fertilizer (F100, F50, F0, and LF). The aim of this study is to figure out the effect of water and organic fertilizer managements on rice performances. Our experiment showed soil Eh was significantly different between three water management treatments (p < 0.05) where FC gained the highest soil Eh, followed by SWD and CF. Whereas, organic fertilizer management gave insignificant effect on soil EH. Under SWD management, number of tillers was significantly higher than CF and FC. On the other hand, water management and organic fertilization had no significant effect on plant height. SWD significantly increased yield and biomass followed by CF and FC. Organic fertilizer caused significant reduction on number of tiller, yield and biomass. In conclusion, SWD provided better environment for rice growth and enhance the rice performances, while the effect of organic fertilizer was not clearly seen.